2022
DOI: 10.3390/molecules27051579
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activities of Plant Extracts against Solanum tuberosum L. Phytopathogens

Abstract: The purpose of the study was to select an environmentally friendly plant biopesticide to protect seed potatoes against phytopathogens. The scope included the evaluation of the antimicrobial activities of 22 plant water extracts, 22 water-glycol extracts, and 3 subcritical carbon dioxide extracts using the agar diffusion method against 10 potato phytopathogens. For the most effective extracts, minimal inhibitory concentration (MIC), chemical composition analysis by gas chromatography–mass spectrometry and in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 48 publications
0
22
0
1
Order By: Relevance
“…Additionally, compound 2 isolated from Rhizoctonia solani could inhibit seed germination that have also been reported ( D’Silva and Herrett, 1971 ). Previous report suggested that furan organic compounds are of bacteriostatic and fungistatic effect on diverse microorganisms ( Vijayakumar and Thirunanasambandham, 2021 ; Steglińska et al, 2022 ). Besides, previous studies had confirmed that microbes could produce different secondary metabolites under different culture conditions ( D’Silva and Herrett, 1971 ; Portela et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, compound 2 isolated from Rhizoctonia solani could inhibit seed germination that have also been reported ( D’Silva and Herrett, 1971 ). Previous report suggested that furan organic compounds are of bacteriostatic and fungistatic effect on diverse microorganisms ( Vijayakumar and Thirunanasambandham, 2021 ; Steglińska et al, 2022 ). Besides, previous studies had confirmed that microbes could produce different secondary metabolites under different culture conditions ( D’Silva and Herrett, 1971 ; Portela et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we evaluated the effect of aqueous garlic extract as a plant biopesticide against mycotoxin-producing fungi that infect potatoes. Several works confirmed the antifungal activity of garlic extracts on Alternaria , Rhizoctonia , Fusarium , Colletotrichum , and Phoma fungi [ 19 , 34 , 35 , 36 ]. The antimicrobial activity of garlic extracts is linked to the production of organosulphur compounds such as allicin, ajoenes, diallyl disulphide, methyl allyl disulphide, and others [ 37 ].…”
Section: Introductionmentioning
confidence: 90%
“…This can be achieved through various biological approaches, e.g., the use of microorganisms and their metabolites, plant extracts, or combined methods with certain synthetic compounds [ 8 ]. In our previous research, we described the inhibition of phytopathogen growth using three biological control agents: lactic acid bacteria [ 17 ], yeast Metschnikowia pulcherrima [ 18 ], and garlic water extract [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the decrease in the number of active substances of fungicides (including bactericides) allowed for use in crop production, concern for the environment, and the development of organic crop production is leading to the development of alternative environmentally friendly pest control systems to combat crop diseases [ 24 ]. The use of natural compounds such as essential oils and plant extracts in plant protection against diseases is promising [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%